Helicity and topological charge tunable optical vortex based on a Hermite-Gaussian beam dynamically controlled folded-cavity resonator - Lin, Shibing; Wang, Deen; Zheng, Yamin; Guo, Liquan; Zhang, Yifan; Zhuang, Yongchen; Huang, Lei (Frontiers in Physics, 2023)
Helicity and topological charge are two important characteristic parameters for vortex beam applications, including optical communications, optical manipulation and material processing, etc. In this work, a helicity and topological charge tunable vortex laser based on a folded resonant cavity is presented. In the resonant cavity, a Z-shaped structure is adopted and two deformable mirrors (DMs) are cascaded into the cavity as intro-cavity modulation elements. By applying different voltage combinations to the DMs, the Hermite-Gaussian (HG) beam with different indices and distribution orientations θ could be generated from the Z-shaped folded-cavity resonator. An extra-cavity astigmatic mode converter is adopted to convert the generated HG beam to the corresponding vortex beam with tunable helicity and topological charge, and the simulation results verified the feasibility of the presented vortex laser. In the experiment, the HGm,0θ beam (m = 1 to 10 and θ = −90 ° to 90 °]) and the vortex beam (topological charge l from ±1 to ±10 and left/right helicity) were flexibly achieved by simply adjusting the driving voltage combinations of the intra-cavity cascaded DMs.